2003
DOI: 10.1128/aem.69.7.4057-4066.2003
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Al to Desulfovibrio desulfuricans

Abstract: The toxicity of Al to Desulfovibrio desulfuricans G20 was assessed over a period of 8 weeks in a modified lactate C medium buffered at four initial pHs (5.0, 6.5, 7.2, and 8.3) and treated with five levels of added Al (0, 0.01, 0.1, 1.0, and 10 mM). At pH 5, cell population densities decreased significantly and any effect of Al was negligible compared to that of the pH. At pHs 6.5 and 7.2, the cell population densities increased by 30-fold during the first few days and then remained stable for soluble-Al conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 45 publications
2
28
1
Order By: Relevance
“…TEM-EDS analysis showed that the precipitates resulting from the biological activity were only formed outside the bacterial cells and were mainly composed by aluminum. In addition, XRD analysis showed that the precipitates were composed by amorphous aggregates, which is consistent with the formation of aluminium hydroxide reported as amorphous (Amonette et al 2003;Berkowitz et al 2005;Mikutta et al 2011). Therefore, the precipitation of aluminum as hydroxide after the lactate consumption could be the mechanism involved in Al removal by DSRB community.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…TEM-EDS analysis showed that the precipitates resulting from the biological activity were only formed outside the bacterial cells and were mainly composed by aluminum. In addition, XRD analysis showed that the precipitates were composed by amorphous aggregates, which is consistent with the formation of aluminium hydroxide reported as amorphous (Amonette et al 2003;Berkowitz et al 2005;Mikutta et al 2011). Therefore, the precipitation of aluminum as hydroxide after the lactate consumption could be the mechanism involved in Al removal by DSRB community.…”
Section: Discussionsupporting
confidence: 64%
“…at the neutral pH values, usually favourable for DSRB growth and activity ), lactate was used in the present study not only as a carbon source but also as an organic ligand that allows maintaining this metal soluble in the nutrient medium. In fact, aluminum lactate (AlLac 3 ) is largely used in toxicology experimentation because it is very soluble in water (Zatta et al 1998;Amonette et al 2003) and the solubility is even maintained at neutral pH (Amonette et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Theses results are in agreement with other studies that have postulated that, under certain conditions, aluminum chloride and sodium metabisulfite may act through cell disruption, compromised membrane permeability, and lipid peroxidation (1,3,6,15,17,34).…”
supporting
confidence: 82%
“…For example, fungi that are more tolerant to the antimicrobial effects of these salts may have greater antioxidant activities that would reduce or nullify the effect of peroxidation by breaking the propagation cycle (8). Furthermore, it is not improbable that other modes of action of aluminum chloride and sodium metabisulfite exist, as other antimicrobial activities of these salts (reactions with protein disulfide groups [4,15,26] and inhibition of enzyme activity through the inactivation of cofactors [30] and coenzymes [23,26,27,28], in the case of sulfites, and replacement of divalent metal complexes [1] and complexation with ATP [11], DNA [31], and phosphates [24], for aluminum) have been reported and cannot be fully explained by lipid peroxidation. This study is the first, to our knowledge, to propose lipid peroxidation as a component of the inhibitory effects of aluminum chloride and sodium metabisulfite on fungal potato pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Aluminum and bisulfite salts are toxic to several microorganisms including fungi (7,15,16) and bacteria (1,8). Aluminum chloride and sodium metabisulfite were shown to be toxic at low concentrations against Erwinia carotovora subsp.…”
mentioning
confidence: 99%